Implementation of six sigma to improve SPIP (Facilities, infrastructure, instalations, and equipment) management at PT Berau Coal - Suprapto, Juny; Yudoko, Gatot (International Journal Labs, 2024)
The commissioning submission process is a significant safety program where contractors must pass a feasibility test to receive an operation feasibility sticker (SKO), ensuring that the unit is safe and ready for operation. The current commissioning process is lengthy and hindered by personnel competence issues and ineffective processes. The research aims to find out how to improve the SPIP management process to be more effective in supporting operational activities at PT Berau Coal but while maintaining mining safety management. A structured approach consisting of multiple phases is outlined, starting with an in-depth analysis of the current SPIP process. The findings are disseminated through formal presentations and reports, aiming to improve efficiency and effectiveness, evaluate centralization feasibility, and develop actionable recommendations for PT BERAU COAL. The proposed solution is to centralize the Commissioning process, improving people, processes, and technology, and eliminating detected waste and defects.